Akad Mudharabah dan Relevansinya dengan Ayat Muamalah pada Transaksi Teknologi Finansial Syariah (TAWAZUN: Journal of Sharia Economic Law, 2023)
Financial technology not only uses a conventional system but also uses a sharia system where one of the contracts is to use a mudharabah contract or the principle of profit sharing. The mudharabah contract itself is part of mu'amalah which of course when it comes to getting a strong argument according to sharia, it must be based on the verses of the Qur'an by understanding the interpretation, especially regarding the interpretation of the muamalah verse. This article aims to discuss the mudharabah contract and its relevance to modern conditions, namely transactions with Islamic financial technology based on the muamalah verse. The research method used is normative research with a qualitative approach. The results of this study are that the mudharabah contract is related to several verses of mu'amalah interpretation, namely Q.S Al-Baqarah: 278-280 and Q.S. An-Nisa: 29 which implies that muamalah transactions must avoid things that are forbidden, one of which is usury. The mudharabah contract is also one of the solutions in the sharia economic system so that transactions do not contain harm and falsehood and the parties in the transaction must like each other (an-tharadhin). The relevance of the Mudharabah Agreement with Modern Transactions is in Sharia Financial Technology where by using sharia principles it can lead to the benefit of the people and avoid harm.